PENGARUH PROFITABILITAS, PERTUMBUHAN ASET DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Asnawati S Nono; Ilyas Lamuda; Zubaidah Rahman (Universitas Bina Taruna Gorontalo, 2024)
The objective of the research is to analyze the influence of profitability, asset growth, and liquidity on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. The usefulness of this research for companies is expected to serve as a consideration for decision-making and to identify the weaknesses and strengths of the company in improving financial conditions during decision-making. The financial data examined spans from 2020 to 2022. The research method employed purposive sampling for sample selection, and the data analysis technique used in this research includes descriptive statistical analysis and multiple linear regression analysis. The results of the study show that the significance value for profitability is 0.001 (which is less than 0.05), and the t-value is 3.558 (which is greater than the t-table value of 2.042). This means that H1 is accepted, indicating that profitability has a significant influence on the capital structure. The significance value for asset growth is 0.322 (which is greater than 0.05), and the t-value is 1.008 (which is less than the t-table value of 2.042). This means that H2 is rejected, indicating that asset growth does not have a significant influence on the capital structure. The significance value for liquidity is 0.000 (which is less than 0.05), and the t-value is -5.175 (which is greater than the t-table value of 1.697). This means that H3 is accepted, indicating that liquidity has a significant influence on the capital structure. The overall significance value is 0.000, which is less than the p-value of 0.05 (0.000 < 0.05), and the F-value is 17.000, which is greater than the F-table value of 2.93. This means that H4 is accepted, indicating that the independent variables, namely profitability, asset growth, and liquidity, have a significant influence on the capital structure.